2003
DOI: 10.1183/09031936.03.00024103
|View full text |Cite
|
Sign up to set email alerts
|

Lung accumulations of eosinophil granulocytes after exposure to cornstarch glove powder

Abstract: Starch is a main component of wheat flour, which, besides being an occupational allergen can also induce irritative symptoms in the airways. A purified starch product (cornstarch glove powder) was used to investigate whether starch alone could induce airway inflammation. The aim of the study was to investigate a role for starch in wheat flour-induced airway inflammation.Ten healthy individuals were exposed to cornstarch glove powder in a whole-body exposure chamber. Bronchoscopy with bronchoalveolar lavage (BA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2003
2003
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 15 publications
1
9
0
Order By: Relevance
“…The results were similar to previous reports of BAL cells in healthy nonsmokers [16], with a majority of the cells characterised as macrophages, and a few as lymphocytes, mast cells or neutrophils. Occasionally, a few epithelial cells could be identified.…”
Section: Bronchoalveolar Lavage Fluid Cell Countssupporting
confidence: 82%
“…The results were similar to previous reports of BAL cells in healthy nonsmokers [16], with a majority of the cells characterised as macrophages, and a few as lymphocytes, mast cells or neutrophils. Occasionally, a few epithelial cells could be identified.…”
Section: Bronchoalveolar Lavage Fluid Cell Countssupporting
confidence: 82%
“…Moreover, healthy individuals exposed to starch showed dramatic signs of lung-accumulated eosinophils after exposure, eosinophils sometimes making up as much as 30% of all BAL fluid cells [21]. The increase in eosinophil numbers correlated with elevated levels of ECP, indicating eosinophil activation on site after exposure [21].…”
Section: Discussionmentioning
confidence: 97%
“…of the allergen-carrying glove powder consisting of cornstarch. GRUNEWALD et al [32] showed that inhalation of cornstarch glove powder leads to subclinical inflammation in the airways in previously unexposed subjects.…”
Section: Discussionmentioning
confidence: 99%